Differential diagnosis of autoimmune pancreatitis from pancreatic cancer by analysis of serum gelatinase levels - Felix, Klaus M.; Dobiasch, Sophie; Gaida, Matthias; Schneider, Kathrin; Werner, Jens; Martens, Erik; Vandooren, Jennifer; Opdenakker, Ghislain (Pancreas, 2016)
ObjectivesThe aim of this study was to analyze serum gelatinases as part of the clinical strategy for the preoperative differentiation between autoimmune pancreatitis (AIP) and pancreatic ductal adenocarcinoma (PDAC). The finding of differential markers will prevent unnecessary surgical resection an
Gesehen am 15.05.2020